RESPON INDONESIA TERHADAP KRISIS PENGUNGSI ROHINGYA PERIODE 2022-2023 - Ahmad Ali Fikri; Jihan Mayola (Emerald: Journal of Economics and Social Sciences, 2024)
This article reviews Indonesia's response to the Rohingya refugee crisis in 2022-2023. The main focus is on government policies, humanitarian efforts and their impact on regional relations. An in-depth analysis of the specific steps taken by the Indonesian government in dealing with the crisis was carried out by examining the latest information. This article also explains Indonesia's diplomatic efforts to gather international support to resolve the Rohingya problem. In addition, this research describes the situation of Rohingya refugees in Indonesia, including the challenges and solutions they face during the integration process. The results of the analysis provide a deeper understanding of the effectiveness of Indonesia's steps in dealing with the Rohingya refugee crisis and its impact on Indonesia's status and role in the local context. In conclusion, this article provides an overview of Indonesia's response to the Rohingya refugee crisis, thus contributing to international understanding of Indonesia's response to this community crisis.